The role of work-life balance in shaping job satisfaction and performance of female employees: a literature review - Dian Intan Tangkeallo; Siti Haerani; Nurdjannah Hamid; Fatmawati Wardihan (Keynesia : International Journal of Economy and Business, 2023)
Work-life balance is one of the issues faced by many organizations and employees, especially female employees. This research aims to determine the role of work-life balance in shaping job satisfaction and performance among female employees. The research method used is a qualitative method based on a review of previous research literature. The results of this study are based on the review or study of literature from national and international journals. The analysis of research journal results shows that work-life balance significantly influences job satisfaction and employee performance. Based on the results of research on female employees in various organizations, it is found that female employees need work-life balance, which will affect their job satisfaction and ultimately improve their performance. This research is limited to studying only female employees, and it is expected that future research will be more varied in terms of employee characteristics.